Perbedaan Pemberian Edukasi dengan Video Tiktok dan Metode Ceramah terhadap Pengetahuan dan Sikap tentang Anemia pada Siswi SMP - Fitriani Fauziah Yelandani; Dyan Kunthi Nugrahaeni; Suhat Suhat; Agus Riyanto; Novie E. Mauliku (Faletehan Health Journal, 2026)
Adolescent girls as prospective mothers are considered to be a priority target to stop the possibility of being women of childbearing age who experience anemia during pregnancy. The incidence of anemia in adolescents is also increasing due to low education regarding balanced nutritional consumption. TikTok social media can be used for health education. This study aimed to determine the differences in Tiktok video media and lecture method regarding education about anemia on knowledge and attitudes of female students of junior high school. This study was conducted on 72 female students of a junior high school in Bandung City, Indonesia. This research is a true experiment with a pretest-posttest and control group design. The results of the study showed an increase in knowledge scores and attitude scores in the TikTok video media group and lecture method group. In the dependent t-test, there was a difference in the level of knowledge in the TikTok video media group and the lecture method group (p = 0.0001). In addition, there was a difference in the attitude of the TikTok video media group (p = 0.0001) and the lecture method group (p = 0.001). The results of the analysis using the ANOVA test showed a a difference in knowledge score (p = 0.0001) and attitude score (p = 0.002) before and after the TikTok video media intervention was given. Thus, TikTok social media can be used as a health education facility with interesting topics around adolescent health. Furthermore, cooperation between schools and health centers is needed to monitor adolescent health.